2020
DOI: 10.3389/fnhum.2020.00366
|View full text |Cite
|
Sign up to set email alerts
|

Transient Amplitude Modulation of Alpha-Band Oscillations by Short-Time Intermittent Closed-Loop tACS

Abstract: Short-Time Intermittent Closed-Loop Alpha EEG-tACS alpha generators. This favors stimulation protocols as well as analysis regimes exploiting inter-individual differences, such as spatial filters to reveal otherwise hidden stimulation effects and, thereby, comprehensively induce and study the effects and underlying mechanisms of tACS.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 96 publications
3
23
0
Order By: Relevance
“…Instead of pre-determining stimulation parameters, from experience and models alone, the parameters are dynamically tuned to the current brain activity in near real time ( Boyle and Frohlich, 2013 ; Wilde et al, 2015 ; Bergmann et al, 2016 ; Karabanov et al, 2016 ; Thut et al, 2017 ). Respective novel approaches of applying frequency and phase specific tACS corresponding to current brain activity have shown promising results in memory consolidation during sleep ( Jones et al, 2018 ; Ketz et al, 2018 ) and phase-dependent modulation of the α-rhythm via closed-loop tACS are currently studied ( Zarubin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead of pre-determining stimulation parameters, from experience and models alone, the parameters are dynamically tuned to the current brain activity in near real time ( Boyle and Frohlich, 2013 ; Wilde et al, 2015 ; Bergmann et al, 2016 ; Karabanov et al, 2016 ; Thut et al, 2017 ). Respective novel approaches of applying frequency and phase specific tACS corresponding to current brain activity have shown promising results in memory consolidation during sleep ( Jones et al, 2018 ; Ketz et al, 2018 ) and phase-dependent modulation of the α-rhythm via closed-loop tACS are currently studied ( Zarubin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The capacity to induce or suppress target oscillatory activities within a relatively short period of time (within several seconds) is a unique and highly valuable feature of our online phase-locking closed-loop tACS system as compared to other currently available tACS techniques. Conventional long-term continuous tACS and recently published brain signal based closed-loop tACS set-ups have to date only reported unidirectional modulation of brain oscillations at the stimulation frequency (24,(44)(45)(46). This inflexibility regarding directionality is problematic for many functions and applications.…”
Section: Discussionmentioning
confidence: 99%
“…Within the alpha-band research, OTA has been reported by several NFB studies (Kluetsch et al, 2014 ; Peeters et al, 2014 ; Nicholson et al, 2016 ; Ros et al, 2017a , b ; Deiber et al, 2020 ) whereas the occurrence of OTA in tACS research is rather ambiguous (Gundlach et al, 2017 ; Haberbosch et al, 2019 ; Krawinkel et al, 2019 ; Zarubin et al, 2020 ). OTA has been attributed to the influence of homeostatic plasticity in both NFB (Kluetsch et al, 2014 ; Peeters et al, 2014 ; Nicholson et al, 2016 ; Ros et al, 2017a , b ; Deiber et al, 2020 ) and tACS research (Garside et al, 2015 ; Gundlach et al, 2017 ; Ketz et al, 2018 ; Haberbosch et al, 2019 ; Zarubin et al, 2020 ). However, to the best to our knowledge, so far, neither tACS nor NFB studies have investigated a direct link between OTA and the neural markers specific for homeostatic plasticity.…”
Section: Aftereffectsmentioning
confidence: 99%
“…This kind of aftereffect has been shown to occur immediately after the termination of intervention by NFB or tACS (Garside et al, 2015;Nicholson et al, 2016;Deiber et al, 2020). Within the alpha-band research, OTA has been reported by several NFB studies (Kluetsch et al, 2014;Peeters et al, 2014;Nicholson et al, 2016;Ros et al, 2017a,b;Deiber et al, 2020) whereas the occurrence of OTA in tACS research is rather ambiguous (Gundlach et al, 2017;Haberbosch et al, 2019;Krawinkel et al, 2019;Zarubin et al, 2020). OTA has been attributed to the influence of homeostatic plasticity in both NFB (Kluetsch et al, 2014;Peeters et al, 2014;Nicholson et al, 2016;Ros et al, 2017a,b;Deiber et al, 2020) and tACS research (Garside et al, 2015;Gundlach et al, 2017;Ketz et al, 2018;Haberbosch et al, 2019;Zarubin et al, 2020).…”
Section: Aftereffects and Their Potential Link With Brain Plasticitymentioning
confidence: 99%